Modelagem matem?tica para a otimiza??o da cin?tica do crescimento de leveduras e produ??o de enzimas e bioetanol - Peixoto, Abra?o Brito (2022)
The objectives of this work were mathematical modeling of enzymatic hydrolysis, bioethanol production and growth pattern of previously selected preparations. The enzyme action was performed by studying the enzyme activity at temperatures of 40, 50, and 60 ?C Two yeast strains (LEB-T07 LEB-AAQ5B) were selected and capable of producing amylase and ethanol, respectively. Yeasts are producing amylases with enzymatic activity of up to 10.41 U/mL. In the second phase, we sought to perform mathematical modeling, inspired by the Boltzmann Transfer Equation. The optimal enzymes for the production of strain LEBT07 were determined: fermentation conditions of 120 h, whose enzymes reach the highest activity (9.19 U/mL) at 60 ?C. LEB-AAQ5B yeast strains exhibit optimal conditions for ethanol production: fermentation time of 220 h under aeration of approximately 0.7 vvm, in which ethanol synthesis is observed at a concentration of 1.4 g/L. To define the kinetic parameters of growth of two strains of Myriangium sp. (Y6511 and Y6512) in Sabouraud medium at temperatures of 26, 30 and 34 ?C at time t ranging from 0 to 36 h. The maximum cell concentration was 34.00 g/L. The maximum specific growth rate was 0.30 h-1 under the growth condition at 26 ?C. The maximum biomass productivity was 2.75 g/L.h at 26 ?C. The observed parameters are suitable for the production of cell mass, in batch or in a continuous process, enzymes and other bioproducts of commercial interest.